Factors that influence tourists visit intention to museums in Malacca - Azlan, Nurun Nadhirah Nor; Saad, Mazni (2019)
The museum has been a cultural bridge between past and future for a long time. Museums reflect a society as they are repositories of historical, unique, valuable and important objects and artefacts. However, in global, museum indicates constant or increasing visit numbers, and the types of people visiting them have remained the same. Instead of understanding visitors, museums are said to focus on organized programs. Most of the museum in Malaysia failed to attract new and recurring visitors when they fail to understand their visitors. At this point, museums need to find out why and what are the factors of visitors’ visitation to museums. This study will be focusing on three objectives which are; 1) To investigate the reasons that influence the visitor’s visitation decision process at museums in Malacca, 2) To identify the type of tourist behind a museum visitation in Malacca. 3) To investigate the main factor of visitors travelling exhibits to museums in Malacca. For this research study, there are 3 elements that will be highlighted that is the factors that might influence the visitors’ intention to museum namely, educational factor, relaxation factor and aesthetics factor. A total of 384 respondents from Malacca museum visitors are participating in this study. The data were analyzed by using IBM Statistical Package for Social Science (SPSS) with several analyses. The result of the findings shows that there are positive relationships between educational factor, relaxation factor and aesthetics factor.